The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jpclett.8b01429
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Transient Charge Density and Metal–Ligand Covalency in Photoexcited Ferricyanide with Femtosecond Resonant Inelastic Soft X-ray Scattering

Abstract: Soft X-ray spectroscopies are ideal probes of the local valence electronic structure of photocatalytically active metal sites. Here, we apply the selectivity of time-resolved resonant inelastic X-ray scattering at the iron L-edge to the transient charge distribution of an optically excited charge-transfer state in aqueous ferricyanide. Through comparison to steady-state spectra and quantum chemical calculations, the coupled effects of valence-shell closing and ligand-hole creation are experimentally and theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 34 publications
3
57
0
2
Order By: Relevance
“…Oscillatory wavepacket motions have been clearly measured in time-resolved WAXS [19,27,32], however the effects of purely nuclear dynamics in ultrafast Kα/Kβ XES has not been observed [10][11][12][13][14]. This contrasts with other X-ray spectroscopic methods that directly involve valence orbitals, such as X-ray absorption [33][34][35][36][37][38] and resonant inelastic X-ray scattering [39][40][41], which are sensitive to both electronic and nuclear structure. The development of ultrafast XES requires understanding the impact of nuclear dynamics on Ka and Kb XES spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Oscillatory wavepacket motions have been clearly measured in time-resolved WAXS [19,27,32], however the effects of purely nuclear dynamics in ultrafast Kα/Kβ XES has not been observed [10][11][12][13][14]. This contrasts with other X-ray spectroscopic methods that directly involve valence orbitals, such as X-ray absorption [33][34][35][36][37][38] and resonant inelastic X-ray scattering [39][40][41], which are sensitive to both electronic and nuclear structure. The development of ultrafast XES requires understanding the impact of nuclear dynamics on Ka and Kb XES spectra.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] While the excited-state potential energy landscape of Fe II complexes can now be routinely tailored, we still lack af undamental understanding of the valence electronic structure of charge-transfer states as the starting point of interfacial charge injection. They are commonly described by alocally oxidized/reduced metal site, [9][10][11] but the quantitative implications on charge and spin distributions are rather elusive.T his is in particular the case in the light of quantum chemical simulations suggesting that oxidizing the transition metal center,that is,reducing the 3d electron count, does not strongly influence its local electronic charge. [12,13] Reconciling these observations with the demonstrated interfacial charge injection from MLCT states of Fe-based dyes [14][15][16] is therefore not only important in terms of af undamental chemical understanding but also for the further development of lowcost and high-efficiency light-harvesting applications.…”
mentioning
confidence: 99%
“…XAS and RIXS spectroscopy applied to metal–ligand complexes can provide an atom‐specific, chemical state selective, crystal field symmetry and orbital symmetry resolved description of the electronic structure . In References , it has been shown that this allows for scrutinizing traditional chemical concepts of metal–ligand bonding.…”
Section: Applicationsmentioning
confidence: 99%